Unsettled times: indigenous incarceration and the links between colonialism and the penitentiary in Canada - Chartrand, Vicki (Canadian journal of criminology and criminal justice, 2019)
The high rate of Indigenous incarceration is a well-documented problem throughout Canada. Within mainstream discourses, this problem is often framed as the legacy or effects of colonialism, which has resulted in the systemic racism and cultural and socio-economic deprivation experienced by Indigenous people today. An increasing body of scholarly literature is challenging the assumption that colonialism is something of the past by looking at how its structures and logics persist today. Thus far, however, little consideration has been given to the colonial context and emergence of Indigenous incarceration in Canada. By tracing the historical links between modern colonialism and the emergence of the Canadian penitentiary into the present, this research reveals some of the hidden connections that contribute to the current rates of Indigenous incarceration and the relationship that continues to exist between colonialism and the penal system today. These findings highlight a socio-politics of incarceration that go beyond a crime and justice framework.